Electronic storefront development using responsive web design (ACECS) / Megat Al Zhahir Daniel Megat Nor Mazlan ... [et al.] - Megat Nor Mazlan, Megat Al Zhahir Daniel; Awang Abu Bakar, Nor Azila; Nik Daud, Nik Marsyahariani; Mohd Sabri, Norlina (Universiti Teknologi MARA, Perak, 2023)
Food and beverage (F&B) businesses often encounter a common issue: employees struggling to manage customer orders efficiently. Moreover, the lack of a computerized system and online presence can result in the physical location becoming overcrowded during peak hours, causing potential customers to be discouraged by lengthy waiting times. To address the issue, the ordering process needs to be computerized for improved efficiency. This study aims to achieve several objectives: identifying user and system requirements for an e-commerce system in F&B businesses, creating and developing a web-based e-commerce system using responsive web design, and evaluating the system's functionality and usability. To initiate this research, a preliminary analysis of system requirements was conducted through surveys and literature review. The design phase followed, producing essential design diagrams such as the data flow diagram (DFD), which plays a crucial role in shaping system functionalities. The implementation's backend employs the MySQL database for effective data storage and PHP for data processing. On the frontend, Figma was used for initial system design, while Bootstrap, cascading style sheets (CSS), and hypertext markup language (HTML) were used to create a functional website. The research culminated in functionality and usability testing. Usability testing involved expert evaluation with input from two experts. The results acquired give a positive indicator for further implementation. This study sheds light on a tool that could enhance the order process in F&B business outlets. Responsive design features were incorporated to ensure a consistent and user-friendly experience across various devices.